Crystallization process of N, 2, 3-trimethyl-2-isopropyl butyramide
Through a process including alkaline washing, reduced pressure concentration and alcohol solvent cooling and crystallization, needle-like WS-23 crystals with low surface energy were obtained, which solved the problem of WS-23 prone to agglomeration in a humid environment, and improved the Product stability and application performance.
Patent Information
- Application Number
- CN202411400620.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
WS-23 is prone to agglomeration in humid environments, resulting in poor storage and transportation stability and affecting its application performance.
A crystallization process is adopted, which includes alkaline washing and deionized water washing using 5% NaOH solution, followed by reduced pressure concentration and frozen water cooling and crystallization, followed by addition of alcohol solvent for a second cooling and crystallization, and finally drying and passing 100 mesh screening was obtained to obtain a needle-like crystalline product of N,2,3-trimethyl-2-isopropylbutylamide, reducing the surface energy and interaction area of the crystal.
It significantly reduces the tendency of clumping, improves the stability and uniformity of the product, simplifies the process flow, improves the purity and yield of the product, and enhances the application performance in the fields of food, medicine and cosmetics.
Smart Images

Figure CN119285488A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of amide compound crystallization, and in particular to a crystallization process of N,2,3-trimethyl-2-isopropylbutyramide. Background Art
[0002] N,2,3-trimethyl-2-isopropylbutyramide (WS-23) is a highly effective cooling agent. Its unique cooling effect is widely used in food, medicine, cosmetics and other fields. The molecular formula of WS-23 is C 10 H 21 NO, chemical structure is Compared with traditional cooling agents such as menthol, WS-23 has significant advantages in providing a long-lasting cooling effect.
[0003] At present, there are two main methods for the synthesis of WS-23. The first method is to use polyphosphoric acid as a catalyst, 2-isopropyl-2,3-dimethylbutyronitrile (DIPPN) and dimethyl carbonate as raw materials, and react under high temperature conditions. The advantage of this method is that the reaction speed is fast and the product can be obtained in a short time, but it is easy to cause side reactions, affecting the purity and yield of the product. Another synthesis method is to use a solid acid catalyst and react at a certain temperature. The advantage of this method is that the reaction conditions are mild, the corrosion to the equipment is small, and it is more suitable for industrial production. The crude WS-23 obtained by these two methods needs to be crystallized to improve the purity of the product. In the existing crystallization process, slow cooling or evaporation of the solvent is usually used for crystal growth, and the resulting crystal forms are mostly long rods and short rods. In addition, different crystal morphologies will affect the packaging, storage and application performance of the product.
[0004] For example, the invention patent with patent publication number CN109912446A discloses a N,2,3-trimethyl-2-isopropylbutanamide crystal with a short rod-like morphology and its crystallization process. By adding seed crystals, a short rod-like crystal morphology with a significantly reduced aspect ratio is obtained, which has better fluidity, thereby achieving the purpose of reducing or preventing product agglomeration. However, since the short rod-like crystals are short and thick, it is easier for the crystals to be physically embedded, especially when stacked on each other, which increases the contact area between the particles. In a humid environment, water molecules gather on the surface of the short rod-like crystals and form tiny liquid bridges, forming adhesion between the crystals, resulting in the short rod-like WS-23 still having a high tendency to agglomerate in a humid or pressure environment. Summary of the invention
[0005] In order to solve the problem that WS-23 is easy to agglomerate in a humid environment mentioned in the above background technology, the present invention provides a crystallization process of N,2,3-trimethyl-2-isopropylbutanamide.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A crystallization process of N,2,3-trimethyl-2-isopropylbutyramide comprises the following steps: S1. The N,2,3-trimethyl-2-isopropylbutanamide mother liquor obtained by production is firstly subjected to alkali washing with a 5% NaOH solution to remove acidic impurities therein, and the alkali washing time is 30 minutes, and then washed with deionized water until the pH value of the washing liquid reaches neutral to ensure the removal of residual alkali and other water-soluble impurities, and then decolorized with activated carbon, filtered to obtain a clear organic phase, concentrated under reduced pressure, opened the refrigerated water for the first cooling and crystallization, and kept warm and stirred for 1-5 hours to obtain a pre-crystallization solution; S2, adding an alcohol solvent to the pre-crystallization solution, performing a second cooling and crystallization, and keeping the temperature and stirring for 1-3 hours to promote further growth of crystals to obtain a wet product of N,2,3-trimethyl-2-isopropylbutyramide, and washing the crystals with a small amount of cold methanol to remove residual mother liquor and impurities; S3. Dry the wet product of N,2,3-trimethyl-2-isopropylbutanamide, and sieve the dried crystals through a 100-mesh sieve to obtain a crystalline product of N,2,3-trimethyl-2-isopropylbutanamide having a needle-like morphology. The overall shape of the crystal is slender, similar to the shape of a needle, but not strictly cylindrical, but has a certain width variation.
[0007] Furthermore, in step S1, the rate of the first cooling and crystallization is 5-10°C / h, and the insulation temperature is -10-0°C.
[0008] Furthermore, in step S2, the rate of the second cooling and crystallization is 2-5°C / h, and the insulation temperature is -10-0°C.
[0009] Furthermore, in step S2, the alcohol solvent is a mixed solvent of an alkane solvent and an alcohol solvent; Wherein, the alkane solvent is selected from one or a combination of petroleum ether, n-heptane, cyclohexane, and n-hexane; The alcohol solvent is selected from one or a combination of methanol, ethanol and isopropanol.
[0010] Preferably, the alkane solvent is selected from petroleum ether, and the alcohol solvent is selected from ethanol.
[0011] Furthermore, the volume ratio of the alkane solvent to the alcohol solvent is 1:(0.1-0.5).
[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention successfully obtains a needle-like crystal morphology that is wide at the top and narrow at the bottom through a unique crystallization process. The needle-like crystal has a smaller cross-sectional area, especially at the lower end of the crystal. Therefore, the interaction area at the contact point of the crystal is significantly reduced, and the interaction force between the crystals is reduced. Especially under wet conditions, the possibility of agglomeration is greatly reduced, and the stability and uniformity of the product are improved.
[0013] 2. Rod-shaped crystals have higher surface energy due to their larger surface area, which increases the tendency to agglomerate in a wet environment. The needle-shaped crystal structure with lower surface energy obtained by this technical solution helps to reduce the interaction between crystals and reduce the tendency to agglomerate. Compared with common rod-shaped crystals, needle-shaped crystals that are wide at the top and narrow at the bottom have lower surface energy. Their morphological design makes the crystal surface area relatively small, thereby reducing the tendency to agglomerate caused by high surface energy in a wet environment, helping to maintain the dispersion of the crystals and improving the stability of the product during storage and transportation.
[0014] 3. This technical solution simplifies the process flow and reduces the complexity of operation, helps reduce production costs, and improves the reliability and repeatability of the process. By optimizing solvent selection and crystallization conditions, higher product purity and yield are achieved.
[0015] 4. The crystal morphology prepared by the present invention has a lower tendency to agglomerate and better fluidity, and thus exhibits higher stability during storage and transportation. This helps to reduce product quality problems and reduced application performance caused by agglomeration, so that WS-23 exhibits better solubility, dispersibility and taste in the fields of food, medicine and cosmetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a physical comparison diagram of Example 1 and Comparative Example 1 in a humid environment; Figure 2 The XRD diffraction patterns of Example 1 and Comparative Examples 1-4 are shown in FIG. Figure 3 is the gas chromatogram of Example 1; Figure 4 is the gas chromatogram of Example 2; Figure 5 It is the gas chromatogram of Comparative Example 1; Figure 6This is a 5x microscope image of Example 1; Figure 7 This is the metallographic structure of Example 1. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] 200 kg of 2-isopropylbutyric acid, 150 kg of 2-methyl-2-aminopropane and 1% of the total weight of p-toluenesulfonic acid of the reactants were added to the reactor, and the mixture was heated to 80° C. under normal pressure for amidation reaction. The reaction was stirred for 4 hours. After the reaction was completed, the reaction mixture was cooled to room temperature, and the obtained organic phase was used as the mother liquor of N,2,3-trimethyl-2-isopropylbutyramide in the example and the comparative example. Example 1
[0020] A crystallization process of N,2,3-trimethyl-2-isopropylbutyramide comprises the following steps: S1. The N,2,3-trimethyl-2-isopropylbutanamide mother liquor obtained above was first alkali-washed with a 5% NaOH solution to remove acidic impurities therein, and the alkali washing time was 30 minutes. Then, it was washed with deionized water until the pH value of the washing liquid reached neutrality to ensure the removal of residual alkali and other water-soluble impurities. Then, activated carbon was used for decolorization. The amount of activated carbon added was 1% of the volume of the solution. The decolorization time was 1 hour. The clarified organic phase was filtered to obtain a clear organic phase, and the vacuum concentration was performed under reduced pressure. The vacuum degree of the reduced pressure concentration was -0.09 MPa, and the temperature was 30°C until the volume of the solution was reduced to 1 / 3 of the original volume. The refrigerated water was turned on for the first cooling and crystallization. The rate of the first cooling and crystallization was 5°C / h. The insulation temperature was -10°C. The mixture was stirred for 1 hour at a stirring speed of 200rpm to obtain a pre-crystallization solution. S2, adding petroleum ether and ethanol in a volume ratio of 1:0.1 to the pre-crystallization solution, and performing a second cooling and crystallization. The rate of the second cooling and crystallization is 2°C / h, the insulation temperature is -10°C, and the temperature is kept and stirred for 1h at a stirring speed of 300rpm to promote further growth of crystals to obtain N,2,3-trimethyl-2-isopropylbutanamide wet product, and the crystals are washed with 1wt% cold methanol to remove residual mother liquor and impurities; S3. Dry the wet product of N,2,3-trimethyl-2-isopropylbutyramide in a vacuum drying oven at 40°C for 12 hours. The dried crystals are sieved through 100 mesh to obtain the finished crystal of N,2,3-trimethyl-2-isopropylbutyramide, which has a needle-like morphology. The purity of the product measured by GC is 99.88%, and the yield is 81.0%. Example 2
[0021] A crystallization process of N,2,3-trimethyl-2-isopropylbutyramide comprises the following steps: S1. The N,2,3-trimethyl-2-isopropylbutanamide mother liquor obtained above was first alkali-washed with a 5% NaOH solution to remove acidic impurities therein, and the alkali washing time was 30 minutes. Then, it was washed with deionized water until the pH value of the washing liquid reached neutrality to ensure the removal of residual alkali and other water-soluble impurities. Then, activated carbon was used for decolorization. The amount of activated carbon added was 1% of the volume of the solution. The decolorization time was 1 hour. The clarified organic phase was filtered to obtain a clear organic phase, and the vacuum concentration was performed under reduced pressure. The vacuum degree of the reduced pressure concentration was -0.1 MPa and the temperature was 60°C until the volume of the solution was reduced to 1 / 3 of the original volume. The refrigerated water was turned on for the first cooling and crystallization. The rate of the first cooling and crystallization was 10°C / h. The insulation temperature was 0°C. The mixture was stirred for 5 hours at a stirring speed of 300rpm to obtain a pre-crystallization solution. S2, adding n-heptane and methanol in a volume ratio of 1:0.5 to the pre-crystallization solution, and performing a second cooling and crystallization, the second cooling and crystallization rate is 5°C / h, the insulation temperature is 0°C, the insulation stirring is 3h, and the stirring speed is 400rpm to promote further growth of crystals to obtain N,2,3-trimethyl-2-isopropylbutanamide wet product, and a small amount of cold methanol is used to wash the crystals to remove residual mother liquor and impurities; S3. Dry the wet product of N,2,3-trimethyl-2-isopropylbutyramide in a vacuum drying oven at 40°C for 12 hours. The dried crystals are sieved through 100 mesh to obtain the finished crystal of N,2,3-trimethyl-2-isopropylbutyramide, which has a needle-like morphology. The purity of the product measured by GC is 99.91%, and the yield is 92.7%.
[0022] Comparative Example 1 This comparative example uses commercially available N,2,3-trimethyl-2-isopropylbutyramide (98%, Cas No. 51115-67-4, MDL No. MFCD00130070), and the purity of the product measured by GC is 98.3%.
[0023] Comparative Example 2 The difference between this comparative example and Example 1 is that no alcohol solvent is added, and the remaining steps are the same as Example 1. The purity of the product measured by GC is 99.3%, and the yield is 71.7%.
[0024] Comparative Example 3 The difference between this comparative example and Example 1 is that the second cooling and crystallization is not performed, and the remaining steps are the same as those in Example 1. The purity of the product measured by GC is 53.1%, and the yield is 42.5%.
[0025] Comparative Example 4 The difference between this comparative example and Example 2 is that no mixed solvent is added, and the remaining steps are the same as those in Example 2. The purity of the product measured by GC is 99.1%, and the yield is 72.8%.
[0026] Comparative Example 5 The difference between this comparative example and Example 2 is that the second cooling and crystallization is not performed, and the remaining steps are the same as those in Example 2. The purity of the product measured by GC is 55.4%, and the yield is 67.2%.
[0027] Referring to the method of GB 25593-2010 "Food Additive N,2,3-Trimethyl-2-isopropylbutyramide", the finished products of Examples 1-2 were tested for performance, and the results are shown in Table 1: Table 1. Physical and chemical properties of the finished products obtained in Examples 1-2
[0028] project Example 1 Example 2 Melting point / % 61 62 Acid value (in KOH) / (mg / g) 0.34 0.32 Content (GC, area normalization method) / % 99.88 99.98 Heavy metal content (in terms of Pb) / (mg / kg) 5.16 4.89 Arsenic (As) / (mg / kg) 0.28 0.37 It can be seen from Table 1 that the finished products obtained in Examples 1-2 all meet the requirements of GB 25593-2010.
[0029] Compared with Comparative Example 1 (commercially available product), the product purity of Examples 1 and 2 is higher and the yield is also quite high, which shows the advantages of the crystallization process of the present invention in terms of purification and yield. Comparative Examples 2 and 4 do not add alcohol solvents or mixed solvents, resulting in a decrease in product purity and a lower yield than the corresponding examples, indicating that alcohol solvents or mixed solvents help to improve the purity and yield of the product during the crystallization process. Comparative Examples 3 and 5 did not perform a second cooling crystallization, resulting in a significant decrease in product purity and a significant decrease in yield.
[0030] See also Figure 1-7 , Figure 1 After being placed in a humid environment (relative humidity of 60% and room temperature) for 12 hours, the sample of Example 1 remained dispersed without agglomeration, while the commercially available WS-23 product of Comparative Example 1 showed obvious agglomeration. This indicates that the WS-23 crystals prepared in Example 1 have better moisture resistance and can maintain better dispersibility and stability in a humid environment.
[0031] Figure 2-5 The XRD diffraction diagram and gas chromatogram illustrate the difference in crystal structure between Example 1 and the comparative example.
[0032] According to gas chromatography, the retention times are 9.985, 9.958, and 9.953, respectively. Compared with the WS-23 standard product, it can be preliminarily determined that the obtained crystal is WS-23 crystal. From the XRD diffraction pattern analysis, the key characteristic peak of the WS-23 product is the diffraction angle 2θ at about 13. The characteristic absorption peak of the homemade sample of Example 1 is higher and more intense than the characteristic peak of the comparative example, indicating that the crystalline phase content of the homemade product is higher. Comparing the width and narrowness of the peak shape of the two, the peak shape of the homemade product is relatively narrow, which means that its crystallinity is higher. In addition, the diffraction angle of the homemade product has a characteristic absorption peak at about 30 and 55, while other products do not have this characteristic peak, indicating that there are differences in the crystal structure, further highlighting the uniqueness of the long needle-shaped crystal. It is known by calculation of the crystal crystallinity that the homemade crystal crystallinity reaches 75.17%. Although other comparative products can reach a crystallinity of more than 70%, they are still different from the homemade products, indicating that the crystal structures of the two are different on a microscopic scale.
[0033] In Figures 6 and 7, the crystals of Example 1 present an obvious needle-like morphology, with a length much greater than a diameter, and the crystals are wide at the top and narrow at the bottom, that is, the top of the crystal (or the start end of growth) is relatively wide, while the bottom (or the end end of growth) gradually narrows. This morphology is conducive to reducing the contact area and interaction between adjacent particles, thereby obtaining smaller nano-sized crystals.
[0034] Compared with Comparative Example 1 (commercially available WS-23 product), the needle-shaped or cubic crystal product of Example 1 (self-made) has lower mass and smaller packing density than powder crystals or rod-shaped crystals at the same volume. Since smaller nano-sized crystals are obtained, the particle size is reduced, thereby giving WS-23 a higher specific surface area (the total area per unit mass is increased), while also reducing the contact area and interaction between adjacent particles. Figure 6 The crystals in the WS-23 have a high specific surface area, that is, a relatively large surface area to volume ratio, which means that more active sites are exposed on the surface, which can effectively increase the contact rate of the cooling agent in the process of compounding with spices, thereby improving the compounding efficiency and the cooling sensation. The needle-shaped crystal structure also facilitates the transmission of electrons, protons and ions inside the crystal, making the cooling sensation of WS-23 more powerful in the mouth.
[0035] In summary, the WS-23 crystals prepared in Examples 1-2 have better moisture resistance, higher specific surface area, and better cooling burst impact, and have broad application prospects.
[0036] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide, characterized in that: The following steps are involved: S1. The produced N,2,3-trimethyl-2-isopropylbutyramide mother liquor is sequentially washed with alkali and water, then decolorized with activated carbon, filtered to obtain an organic phase, concentrated under reduced pressure, opened the refrigerated water for the first cooling and crystallization, and kept warm and stirred for 1-5 hours to obtain a pre-crystallization solution; S2, adding the pre-crystallization solution to the mixed solvent, cooling and crystallizing for the second time, and stirring at the temperature for 1-3 hours to obtain a wet product of N,2,3-trimethyl-2-isopropylbutyramide; S3. Dry the wet product of N,2,3-trimethyl-2-isopropylbutanamide to obtain a crystalline product of N,2,3-trimethyl-2-isopropylbutanamide having a needle-like morphology.
2. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: The rate of the first cooling and crystallization in step S1 is 5-10°C / h, and the insulation temperature is -10-0°C.
3. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: In step S1, the amount of activated carbon added is 1% of the solution volume, and the decolorization time is 1 h.
4. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: The vacuum degree of reduced pressure concentration in step S1 is -0.09-(-0.1) MPa, and the temperature is 30-60° C., until the volume of the solution is reduced to 1 / 3 of the original volume.
5. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: The rate of the second cooling and crystallization in step S2 is 2-5°C / h, and the insulation temperature is -10-0°C.
6. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: The stirring speed in step S1 is 200-300 rpm, and the stirring speed in step S2 is 300-400 rpm.
7. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: In step S2, the mixed solvent is a mixture of an alkane solvent and an alcohol solvent; Wherein, the alkane solvent is selected from one or a combination of petroleum ether, n-heptane, cyclohexane, and n-hexane; The alcohol solvent is selected from one or a combination of methanol, ethanol and isopropanol.
8. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 7, characterized in that: The volume ratio of alkane solvent to alcohol solvent is 1:(0.1-0.5).
9. A crystallization process for N,2,3-trimethyl-2-isopropylbutyramide according to claim 1, characterized in that: During the drying in step S3, the mixture is dried in a vacuum drying oven at 30-50° C. for 10-20 hours.
Citation Information
Patent Citations
2-isopropyl-N,2,3-trimethylbutyramide crystals with short rod-like morphology and crystallization process of 2-isopropyl-N,2,3-trimethylbutyramide crystals
CN109912446A